2021
DOI: 10.25259/sni_539_2021
|View full text |Cite
|
Sign up to set email alerts
|

Identification and surgical ligation of spinal CSF-venous fistula

Abstract: Background: CSF-venous fistulas (CVF) may cause incapacitating positional headaches resulting from spontaneous intracranial hypotension/hypovolemia (SIH). Their etiology remains unknown, although unrecognized local trauma may precipitate SIH. In addition, they are diagnostically challenging despite various imaging tools available. Here, we present CVF identification using magnetic resonance myelography (MRM) and elaborate on their surgical management techniques. Methods: Retrospective charts of confirmed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Wang et al 9 performed open CVF ligation in 20 patients with consecutive reduction of symptoms in all patients and in absence of surgical complications. Another study, by Majeed et al, 14 demonstrated similarly positive results in a series of 6 patients who underwent open surgical ligation of CVF via clipping. All patients showed resolution of their symptoms by applying the same clipping technique as described in our study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Wang et al 9 performed open CVF ligation in 20 patients with consecutive reduction of symptoms in all patients and in absence of surgical complications. Another study, by Majeed et al, 14 demonstrated similarly positive results in a series of 6 patients who underwent open surgical ligation of CVF via clipping. All patients showed resolution of their symptoms by applying the same clipping technique as described in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Beyond this surgical technique, there are standard treatment options for CVF, including EBP, endovascular embolization, and open surgery. 4 , 9 , 14 , 16 Given the novelty of CVF and the lack of randomized controlled trials, the treatment of choice relies on the physician’s preference and expertise or the center’s available modalities. As observed in our cohort, some patients do not respond to interventional measures such as EBP or endovascular embolization and remain symptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case series and clinical studies reporting the outcomes after surgery for SIH are presented in Table 5. Most patients after neurosurgical treatment remained asymptomatic, and the successful rate for operation of SIH varied between 82.6-100% [1,27,43,47,51,54,56,[58][59][60]. Only one case series presented a successful rate of 50% for SIH symptom relief [51].…”
Section: Management Of Spontaneous Intracranial Hypotension Syndrome ...mentioning
confidence: 99%
“…In most studies, most of the affected individuals who underwent surgery were women, and the female-to-male ratio was almost 2:1 [1,43,51,54,[58][59][60]. The patients operated for SIH were in their fourth or fifth decades of life [1,6,11,54,59,60]. In almost all cases, MRI was used to diagnose SIH, which remains the basic diagnostic tool [1,5,54,61,62].…”
Section: Management Of Spontaneous Intracranial Hypotension Syndrome ...mentioning
confidence: 99%